Characterization of epoxy/ waste banana skin fruit with inorganic filler composite upon crack propagation - Nuraina Jasril (2015)
This study is focused to investigate the characterization properties of polymer thin film (epoxy/ banana skin fruit with talc as a filler) for bio composite and the crack propagation of polymer thin film (epoxy/banana skin fruit with talc) bio composite upon oven exposure. Waste banana skin fruit were processed to become banana pulp. Then the thin films were produced by using hand lay-up method. The thickness of the thin film was around 0.10mm to 0.15mm. These thin films were continuously exposed at temperature to determine the weight loss and crack propagation of polymer thin film. The temperatures used are 50°C, 100°C, 150°C, and 200°C, for 600 minutes. The weight losses of thin film were calculated and the cracks on the surface of thin film were observed by visual observation and optical microscope observation. From the study, the changes of thin film surface were observed from smooth surface to rough surface upon oven temperature. The cracks that occur on the surface of thin film were cause by external factor such as stress applied on the thin film and the present of dust particles. As the temperature and exposure time increased, the weight losses were also increased and the cracks become worse. This is because, when the materials were exposed to the heat, the structures of the material become weaken. Oven temperature was given out heat that can break the bonds of the materials. Thus the longer the materials exposed to the heat, the weaken strength of the material.